Pengaruh Relaksasi Pernapasan Terhadap Intensitas Nyeri Pada Persalinan Kala I Di PMB Erlina Herawati Tahun 2023 - Kamelia Sinaga; Citra Anugerah; Azri Yani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Maternal who is difficult to adapt to the pain of labor can cause uncoordinated uterine contractions which can lead to prolongation of the first stage of labor and impaired fetal well-being. The purpose of this study was to see whether there was an effect of respiratory relaxation on the intensity of the first stage labor pain in the maternal love clinic Erlina Herawati, sub-district in 2023. This type of quantitative research used the One Group Pre Test- Post Test Design method with a population of all inpartum mothers in April 2023- June 2023 and a sample of 15 respondents. The results that have been obtained during the study including before the treatment showed mild pain by 2 respondents (13.3%), moderate pain by 6 respondents (40.0%), severe pain by 7 respondents (46.7%). Meanwhile, after treatment of mild pain 8 respondents (53.3%), moderate pain 4 respondents (26.7%), severe pain 3 respondents (20.0%). From the results of the study, it was found that the effect of before being treated and after being treated had a significant change in pain in the mother in labor. Therefore, it is hoped that in the future midwives in clinics will be able to facilitate mothers in giving birth by relaxing breathing it can reduce pain during labor, especially during the first stage of labor.